Herpesvirus Entry Mediator on Radiation-Resistant Cell Lineages Promotes Ocular Herpes Simplex Virus 1 Pathogenesis in an Entry-Independent Manner - Rebecca G. Edwards (American Society for Microbiology, 2015)
ABSTRACT Ocular herpes simplex virus 1 (HSV-1) infection leads to a potentially blinding immunoinflammatory syndrome, herpes stromal keratitis (HSK). Herpesvirus entry mediator (HVEM), a widely expressed tumor necrosis factor (TNF) receptor superfamily member with diverse roles in immune signaling, facilitates viral entry through interactions with viral glycoprotein D (gD) and is important for HSV-1 pathogenesis. We subjected mice to corneal infection with an HSV-1 mutant in which HVEM-mediated entry was specifically abolished and found that the HVEM-entry mutant produced clinical disease comparable to that produced by the control virus. HVEM-mediated induction of corneal cytokines, which correlated with an HVEM-dependent increase in levels of corneal immune cell infiltrates, was also gD independent. Given the complexity of HVEM immune signaling, we used hematopoietic chimeric mice to determine which HVEM-expressing cells mediate HSV-1 pathogenesis in the eye. Regardless of whether the donor was a wild-type (WT) or HVEM knockout (KO) strain, HVEM KO recipients were protected from ocular HSV-1, suggesting that HVEM on radiation-resistant cell types, likely resident cells of the cornea, confers wild-type-like susceptibility to disease. Together, these data indicate that HVEM contributes to ocular pathogenesis independently of entry and point to an immunomodulatory role for this protein specifically on radiation-resistant cells. IMPORTANCE Immune privilege is maintained in the eye in order to protect specialized ocular tissues, such as the translucent cornea, from vision-reducing damage. Ocular herpes simplex virus 1 (HSV-1) infection can disrupt this immune privilege, provoking a host response that ultimately brings about the majority of the damage seen with the immunoinflammatory syndrome herpes stromal keratitis (HSK). Our previous work has shown that HVEM, a host TNF receptor superfamily member that also serves as a viral entry receptor, is a critical component contributing to ocular HSV-1 pathogenesis, although its precise role in this process remains unclear. We hypothesized that HVEM promotes an inflammatory microenvironment in the eye through immunomodulatory actions, enhancing disease after ocular inoculation of HSV-1. Investigating the mechanisms responsible for orchestrating this aberrant immune response shed light on the initiation and maintenance of HSK, one of the leading causes of infectious blindness in the developed world.